A review on ADHD disorder, diagnosis and therapeutic approach in children and adolescents - Gaurav Kumar; Bhawna Sharma; Raj Kumar Tiwari; Ravi Kumar; Maneesh Kumar Singh (Brain-Apparatus Communication)
Attention-deficit/hyperactivity disorder (ADHD) describes a heterogeneous condition that has negative consequences for brain neurodevelopment. ADHD individuals have a variety of traits, including inattention, impulsiveness, and hyperactivity. The collection of articles on ADHD was found in Google Scholar, PubMed, and Research Gate and has been selected for consideration based on evidence that, with early therapy and diagnosis, there is potential to change connections between neurons and improve symptoms. Cognitive behavioral therapy is one of the proven, evidence-based therapies for ADHD in teenagers. This review’s main objective is to examine FDA-approved therapy alternatives for ADHD that are both clinical and non-clinical drugs. The dopaminergic and noradrenergic systems in the frontal cortex, as well as the dopaminergic system in the basal ganglia, are the targets of these therapies in children and adolescents. The study also outlines current research problems and gaps in the available data while offering insights into ongoing initiatives to produce new ADHD treatments.